Pengaruh terapi kognitif terhadap tingkat kecemasan dan ketergantungan activity daily living (ADL) pada pasien gangguan jiwa - Ibrahim Rahmat (Universitas Aisyiyah Yogyakarta, 2016)
This study aimed to determine changes in the level of anxiety and the level of dependency Activity Daily Living ( ADL ) after cognitive therapy in patients with mental disorders. This research method is Quasi Experiment study, pretest and posttest mean cognitive design.Therapy can reduce the level of anxiety, while not statistically significant for patients with mental disorders at the Hospital Grhasia DIY. As for the fulfillment ADL disorders in patients with mental disorders either average or of calculation is statistically significantly may improve fulfillment ADL independently. The results study can suggested to readers that: Hospitals should promote cognitive therapy for patients with depression and anxiety disorder ADL compliance.